Customized biomimetic scaffolds created by indirect three-dimensional printing for tissue engineering - Lee, Ju-Yeon (2013)
Three-dimensional printing (3DP) is a rapid prototyping (RP) technique that can create complex 3D structures by inkjet printing of a liquid binder onto powder biomaterials for tissue engineering scaffolds. Direct fabrication of scaffolds from 3DP, however, imposes a limitation on material choices by manufacturing processes. In this study, we report an indirect 3DP approach wherein a positive replica of desired shapes was printed using gelatin particles, and the final scaffold was directly produced from the printed mold. To create patient-specific scaffolds that match precisely to a patient’s external contours, we integrated our indirect 3DP technique with imaging technologies and successfully created custom scaffolds mimicking human mandibular condyle using polycaprolactone (PCL) and chitosan (CH) for potential osteochondral tissue engineering. To test the ability of the technique to precisely control the internal morphology of the scaffolds, we created orthogonal interconnected channels within the scaffolds using computer-aided-design (CAD) models. Because very few biomaterials are truly osteoinductive, we modified inert 3D printed materials with bioactive apatite coating. The feasibility of these scaffolds to support cell growth was investigated using bone marrow stromal cells (BMSC). The BMSCs showed good viability in the scaffolds, and the apatite-coating further enhanced cellular spreading and proliferation. This technique may be valuable for complex scaffold fabrication.